Comparison of the effects of atorvastatin or fenofibrate on nonlipid biochemical risk factors and the LDL particle size in subjects with combined hyperlipidemia - Melenovsky, Vojtech; Malik, Jan; Wichterle, Dan; Simek, Jan; Pisarikova, Alexandra; Skrha, Jan; Poledne, Rudolf; Stavek, Petr; Ceska, Richard (American heart journal, 2002)
BACKGROUND: Combined hyperlipidemia (CH) is an increasingly prevalent risk factor for premature heart disease, and its treatment is troublesome. The aim of this study was to compare the effects of atorvastatin and fenofibrate on nonlipid biochemical risk factors and the low-density lipoprotein (LDL) particle size in subjects with CH. METHODS: Twenty-nine middle-aged men with CH were randomly assigned to open-label therapy with atorvastatin (10 mg daily) or micronized fenofibrate (200 mg daily); they were sequentially treated with both drugs, with crossover of medication after 10 weeks. RESULTS: Atorvastatin was more efficient in the reduction of total cholesterol, whereas fenofibrate was more efficient in the reduction of triglycerides. Only atorvastatin led to a significant reduction of LDL cholesterol and apolipoprotein B. Only fenofibrate increased high-density lipoprotein cholesterol. Neither drug influenced lipoprotein(a). Mean LDL particle size increased both after fenofibrate (3.08%) and atorvastatin (1.77%). Fenofibrate increased serum homocysteine (HCY) by 36.5%. Atorvastatin had no effect on HCY. Only atorvastatin increased fibrinogen by 17.4%. Only fenofibrate reduced C-reactive protein by 51.7%. Neither drug influenced HOMA (homeostasis model assessment) index of insulin resistance. The plasma level of thiobarbituric acid reactive substances, an index of oxidative stress, decreased after both treatments. CONCLUSIONS: Both atorvastatin and fenofibrate had similar beneficial effects on LDL particle size and on oxidative stress. The effects of both drugs on other parameters such as triglycerides, total and high-density lipoprotein cholesterol, fibrinogen, or HCY differed significantly. These differences, together with the risk profile of a patient, should be considered during selection of a particular lipid-lowering modality.
Keywords: fibrinogen; Atorvastatin; cholesterol; Fenofibrate; klinické křížové studie; familiární kombinovaná hyperlipidemie; LDL-cholesterol; C-Reactive Protein; Cholesterol, LDL; triglyceridy; Triglycerides; lidé; Heptanoic Acids; Hyperlipidemia, Familial Combined; Apolipoproteins B; Cross-Over Studies; Cholesterol; Humans; Risk Factors; Male; Hypolipidemic Agents; Pyrroles; atorvastatin; hypolipidemika; kyseliny heptylové; apolipoproteiny B; HDL-cholesterol; rizikové faktory; fenofibrát; lidé středního věku; C-reaktivní protein; Fibrinogen; mužské pohlaví; pyrroly; Middle Aged; Cholesterol, HDL